“The Undiscovered Country”, “A Kind Behind the Door”, “Neverland”, or “A Small Unfocused Blur”: Uncanny literary definitions of death - Małecka, Katarzyna (Adam Mickiewicz University, 2012)
Known yet unknown, undiscovered yet constantly discovered and re-discovered, death has always been a gold mine providing ideas, work and wages for scientists, sociologists, philosophers, artists, literary critics, and many others who find life’s provisionality in any way “uncanny”. This article looks at select literary definitions of death that present mortality as a concept both familiar and unfamiliar, comforting and discomforting, domestic and strange. Like the Freudian term “uncanny”, the nature of mortality is complex, mysterious and elusive. As Terry Eagleton (2003: 211) points out, “[d]eath is both alien and intimate to us, neither wholly strange nor purely one’s own”. While some of Freud’s ideas from his essay “The ‘Uncanny’” are used as the basis for discussion here, this analysis is not limited to a psychoanalytic perspective and includes psychological, sociological, medical and literary references which help explore different aspects of death in literature.